HMO-primed bifidobacteria exhibit enhanced ability to adhere to intestinal epithelial cells - Walsh, Clodagh; Owens, Rebecca A.; Bottacini, Francesca; Lane, Jonathan A.; van Sinderen, Douwe; Hickey, Rita M. (Frontiers in Microbiology, 2023)
The ability of gut commensals to adhere to the intestinal epithelium can play a key role in influencing the composition of the gut microbiota. Bifidobacteria are associated with a multitude of health benefits and are one of the most widely used probiotics for humans. Enhanced bifidobacterial adhesion may increase host-microbe, microbe-nutrient, and/or microbe-microbe interactions, thereby enabling consolidated health benefits to the host. The objective of this study was to determine the ability of human milk oligosaccharides (HMOs) to enhance bifidobacterial intestinal adhesion in vitro. This study assessed the colonisation-promoting effects of HMOs on four commercial infant-associated Bifidobacterium strains (two B. longum subsp. infantis strains, B. breve and B. bifidum). HT29-MTX cells were used as in vitro intestinal models for bacterial adhesion. Short-term exposure of four commercial infant-associated Bifidobacterium strains to HMOs derived from breastmilk substantially increased the adherence (up to 47 %) of these probiotic strains. Interestingly, when strains were incubated with HMOs as a four-strain combination, the number of viable bacteria adhering to intestinal cells increased by > 90%. Proteomic analysis of this multi-strain bifidobacterial mixture revealed that the increased adherence resulting from exposure to HMOs was associated with notable increases in the abundance of sortase-dependent pili and glycosyl hydrolases matched to Bifidobacterium bifidum. This study suggests that HMOs may prime infant gut-associated Bifidobacterium for colonisation to intestinal epithelial cells by influencing the expression of various colonization factors.